(untitled) (ModaPalavra e-periódico, 2013)
The paper presents research results about methods of printing on fashion fabrics. It points out the processes and productive strategies with the primary objective of designing an overview of the state of the art of contemporary textile printing under the approach of electronic technologies and the construction of theoretical formulations on the subject. The paper was developed starting from a literature review, technical visits, interviews, experiments, tests and discussion of the results.